IR THERMOGRAPHY in Multiphysics Applications - Khawaja, Hassan (UiT The Arctic University of Norway, 2018)
It is seen that Infrared (IR) thermography is becoming one of the very popular and effective methods in the industry as well as research and development sectors. IR thermography being a remote non-contact/non-destructive means of testing is perfectly suitable for tests in extreme environments. In addition, it is fast, reliable and detailed. Due to the advantages offered by IR thermography, it is becoming extremely popular in a number of industries. Not only industry but academic and research institutions are also finding IR thermography as one of the fundamental tools in their arsenal for teaching as well as research. The proposed presentation discusses three case studies where IR thermography has been used effectively in research and development projects at the UiT-The Arctic University of Norway. The first case is about the determination of ice properties using IR thermography in conjunction with three-dimensional finite difference solution of the heat equation. In this study, thermal conductivity and heat transfer coefficient were found for fresh water and seawater ice. The results revealed the difference in the properties. The results were found to be in close agreement with the literature. The second case study presents the estimation of thermal insulation (IREQ) of different types of thermal clothing. The results clearly showed the difference between the insulation ability of sweaters, summer jackets and winter jackets. The third case presents tensile testing of steel samples with IR thermography of the samples. It was a noticed that steel samples were about 20-25°C warmer at the time of failure.